Efek Sosial Media Marketing dan Ulasan Pelanggan terhadap Branding dan Penjualan Parfum HMNS - Muhammad Arif; Firman Darussalam; Aditya Faziawan Azhar; April Laksana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research aims to reveal the impact of social media marketing and customer reviews on branding and sales of HMNS perfume products. Using the Literature Review and Systematic Literature Review research methods, This research identifies how social media marketing and customer reviews influence consumer perceptions of branding and decisions in purchasing HMNS perfume products. The research results show that social media marketing and customer reviews can increase branding awareness, strengthen the brand image, and encourage increased product sales. This research also found that consumers who were involved in a social media campaign were more likely to make a purchase than brands who were not exposed to it.